The Impact of Government Spending on GDP in a Remitting Country - Almukhtar Al-Abri; Ismail H. Genc; George S Naufal (Institute of Labor Economics (IZA), 2018)
The literature on remittances is large and growing. However, its focus has mainly been on the effects of remittance inflows on the receiving economies. Little has been done on the sending economies. In this paper, we use data from Saudi Arabia, one of the top remitting countries in the world, to identify the impact of government spending on Saudi Arabia's real output considering the role of remittance outflows. The results suggest that remittance outflows have a weak effect, if at all, on government spending, which, in turn, has an insignificant impact on GDP. The paper discusses some policy implications.
Keywords: C23; E61; F24; N15; 330; remittances; multipliers; fiscal policy; GCC